2012
DOI: 10.1126/science.1226028
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Division of Drosophila Male Germline Stem Cell Shows Asymmetric Histone Distribution

Abstract: Stem cells can self-renew and generate differentiating daughter cells. It is not known whether these cells maintain their epigenetic information during asymmetric division. Using a dual-color method to differentially label “old” versus “new” histones in Drosophila male germline stem cells (GSC), we show that preexisting canonical H3, but not variant H3.3, histones are selectively segregated to the GSC whereas newly synthesized histones incorporated during DNA replication are enriched in the differentiating dau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
195
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(212 citation statements)
references
References 31 publications
(22 reference statements)
16
195
1
Order By: Relevance
“…Further investigation is required to test these ideas. Intriguingly, a similar phenomenon was recently reported in the Drosophila male germ line (48,49), where the germ line stem cells (GSCs) undergo asymmetric cell division to generate one GSC and one differentiating daughter cell. Chen and coworkers (48) discovered that old/pre-existing canonical histone H3 but not H3.3 were selectively segregated to the daughter GSC.…”
Section: Mass Spectrometry Provides a Powerful Tool To Study Dynamicsmentioning
confidence: 91%
See 1 more Smart Citation
“…Further investigation is required to test these ideas. Intriguingly, a similar phenomenon was recently reported in the Drosophila male germ line (48,49), where the germ line stem cells (GSCs) undergo asymmetric cell division to generate one GSC and one differentiating daughter cell. Chen and coworkers (48) discovered that old/pre-existing canonical histone H3 but not H3.3 were selectively segregated to the daughter GSC.…”
Section: Mass Spectrometry Provides a Powerful Tool To Study Dynamicsmentioning
confidence: 91%
“…They further showed that H3T3ph was required for the asymmetric inheritance of H3, and they suggested it was required in a specific time window (prophase to metaphase) (49). The asymmetric cell division is only limited to Drosophila GSCs and is not seen in surrounding somatic tissues, so is the asymmetric distribution of H3T3ph and directional inheritance of histone H3 (48,49). However, the observations are highly similar to ours in this study that mitotic histone ph mark(s) is(are) enriched on the old histones in early mitosis, suggesting the underlying mechanism is conserved between Drosophila and humans.…”
Section: Mass Spectrometry Provides a Powerful Tool To Study Dynamicsmentioning
confidence: 99%
“…By labeling the budding yeast Saccharomyces cerevisiae genome for one cell cycle by incorporating 5-bromo-deoxyuridine nucleotide analog, then analyzing chromosomes of mother cells separated from those of daughter cells, it was recently reported that there is no mother-daughter bias in segregation of specific strands of any chromosome (Keyes et al 2102). In contrast, it was recently reported that preexisting histones are selectively retained in Drosophila male germline stem cells, while newly synthesized histones are enriched in the differentiating daughter cell (Tran et al 2012). Thus, an active area of research is aimed at determining the strand segregation pattern and exploring their significance in biology at large.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, parental nucleosomes have been shown to be located within B400 bp of their original positions after the completion of the cell cycle 7,35,39 , close to the most probable loop size. DNA loop formation may also be facilitated by the configuration 40 of nascent dsDNA strands as they emerge from the replisome, which would contribute to the partitioning 19,41 of nucleosomes between the two daughter strands by coordinating nucleosome transfer with DNA synthesis 42 .…”
Section: Discussionmentioning
confidence: 99%